Indicators Of Oxidative Stress In Long-Lived Individuals Belonging To The Municipality Of Santa Clara - Fernández-Caraballo, Douglas; Herrera Martínez, Manuela; Heredia Ruiz, Danay; Chaviano Machado, Sonia; González Rodríguez, Emilio (Revista Cubana de Investigaciones Biomédicas, 2019)
Objetive: To determine indicators of oxidative stress in long-lived individuals. Methods: 120 subjects were studied and two groups were formed: 50 individuals older than 85 years of nuclear families and 70 adults under 60 years old taken as a control group, all belonging to the municipality of Santa Clara. Indicators of antioxidant defense status included enzymatic activities superoxide dismutase (SOD) and catalase (CAT), as well as reduced glutathione (GSH) concentrations. The determinations were made with the use of spectrophotometric techniques, and the comparisons between the groups were made through the statistical program SPSS with a level of significance of 95%. Results: The activity of the antioxidant enzyme SOD and GSH levels showed significant differences when comparing both study groups. In the case of the SOD enzyme, the group of long-lived individuals showed a significant reduction in their activity compared to the controls, while GSH levels also decreased in this group. The CAT enzyme activity showed no significant differences between the two study groups. Conclusions: The decrease in enzymatic activity SOD accompanied by a decrease in GSH levels could be an indicator of a state of oxidative imbalance in individuals older than 85 years, which increases their susceptibility to the action of reactive oxygen species.